2011
DOI: 10.5830/cvja-2010-080
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of omega-3 fatty acid content of South African fish oil supplements

Abstract: IntroductionSubstantial evidence describes the protective effects of marine-derived omega-3 (n-3) polyunsaturated fatty acids (PUFA) on cardiovascular diseases as well as many other conditions. Numerous fatty acid preparations are marketed for supplementing the Western diet, which is low in n-3 fats. Since these preparations may vary in their n-3 PUFA content, we tested 45 commercially available products on the South African market for their fatty acid composition.MethodForty-five commercially available n-3 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 24 publications
(18 reference statements)
3
34
1
Order By: Relevance
“…CD values were compared against reference values as described by Opperman et al 13 Peroxide levels were determined spectrophotometrically as described by Khodaparast et al 15…”
Section: Methodsmentioning
confidence: 99%
“…CD values were compared against reference values as described by Opperman et al 13 Peroxide levels were determined spectrophotometrically as described by Khodaparast et al 15…”
Section: Methodsmentioning
confidence: 99%
“…The data derived from fish oils acquired in 13 countries are also compatible with peroxide values of dietary supplement ω-3 oils on the Norwegian Health Care Market, where only 4 of 56 had peroxide values <5 mEq/kg and 28 had <10 mEq/kg [41] as specified by the European Pharmacopeia [42]. The problem of oxidation products in dietary supplement fish oils has been addressed also in a South African study, where the conjugated diene level was used as an indication of rancidity [43]. In the present study, alkenals were determined, which are part of VOCs and responsible for the adverse smell and other potentially harmful effects.…”
Section: Discussionmentioning
confidence: 96%
“…Several publications have studied the correctness of the manufacturers' information in fish oil supplements (Opperman et al, ; Osadnik and Jaworska, ; Yi et al, ). For example, Osadnik et al found that, for the majority of their tested products in the Polish market, there was consistency in the total amount of DHA and EPA claimed on the label, while Opperman's group reported that the n‐3 supplements available in the South African market contained ≤89% of the stated content.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several studies that analyze dietary supplements to provide guidance for consumers, many of them have limitations. For example, in their extraction and derivatization of the FA, they follow multistep procedures and/or involve long heating times (among others, Opperman et al, ), high temperatures (Rincón‐Cervera et al, ), costly automated instrumentation (Roberts, et al, ; Stuff and Whitecavage, ), high‐resolution equipment (Osadnik and Jaworska, ), or special analysis software (Kanable et al, ). Many of them have been conducted in other countries and only concentrate in supplements obtained in local markets (Opperman et al, ; Osadnik and Jaworska, ; Yi et al, ).…”
Section: Introductionmentioning
confidence: 99%